2006
DOI: 10.1002/ijc.21335
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with WST09 (Tookad): Quantitative studies in normal colon and transplanted tumours

Abstract: Photodynamic therapy (PDT) is attracting increasing interest for the safe destruction of localised tumours in a range of organs. However, most photosensitising drugs require a delay of hours to days between drug administration and light activation with skin photosensitivity that may last for weeks. WST09 (Tookad) is a new faster acting photosensitiser that clears within a few hours. In normal rat colon, after sensitisation with an intravenous bolus of WST09, light was delivered to a single point on the mucosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The large extinction coefficient (Ͼ100,000 M Ϫ1 cm Ϫ1 ) typical of the bacteriochlorin Q y band is also advantageous for strong absorption of near-infrared light by the photosensitizer. The Pd-containing bacteriochlorins known as TOOKAD (13,57) and Stakel (2) have been extensively investigated in laboratory studies, and, in addition, TOOKAD has been studied in clinical trials of PDT for prostate cancer (54).…”
Section: Discussionmentioning
confidence: 99%
“…The large extinction coefficient (Ͼ100,000 M Ϫ1 cm Ϫ1 ) typical of the bacteriochlorin Q y band is also advantageous for strong absorption of near-infrared light by the photosensitizer. The Pd-containing bacteriochlorins known as TOOKAD (13,57) and Stakel (2) have been extensively investigated in laboratory studies, and, in addition, TOOKAD has been studied in clinical trials of PDT for prostate cancer (54).…”
Section: Discussionmentioning
confidence: 99%
“…PDT may also stiumulate shutdown of the tumour vasculature (Fingar et al 1999, Engbrecht et al 1999, Chen et al 2002, Woodhams et al 2006 and, in addition, PDT is shown preclinically to activate antitumour immunity (Castano et al 2006, Kousis et al 2007. Recently, photochemicallyinduced anti-tumour immunity was demonstrated in a patient with recurrent angiosarcoma, where distant non-treated tumours disappeared after PDT (Thong et al 2007).…”
Section: Pdt Mediated Targeting Of Tumoursmentioning
confidence: 99%
“…Exposure of vessel basement membrane as a result of endothelial retraction might be only one of the mechanisms causing thrombi formation. Other mechanisms, such as release of thromboxane from platelets (33) and von Willebrand factor from damaged endothelial cells (34), could also contribute to the thrombosis process.…”
Section: Discussionmentioning
confidence: 99%